Analysis of Clinical Evidence and Latest Fantastic Four Guidelines in Heart Failure Management - Fatimah, Ananda Siti (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Heart failure with reduced ejection fraction (HFrEF) is a leading global cause of illness and death. Although treatments exist, recurrence and mortality rates remain high. The Fantastic Four therapy—combining ARNI, beta-blockers, MRAs, and SGLT2 inhibitors—has proven effective in improving outcomes. However, its implementation faces challenges such as clinical, regulatory, and access barriers, as well as limited understanding among healthcare providers. This research aims to analyze the latest clinical evidence underlying the recommendation for using the Fantastic Four in heart failure management, as well as to evaluate its suitability and implications for clinical practice. The research method used is a qualitative approach through literature review, with analysis stages including data screening, data presentation, and conclusion drawing. Research findings indicate that all four classes of medications are highly effective in reducing cardiovascular mortality and hospitalization rates in patients with HFrEF. The latest guidelines from the ESC 2021 and ACC/AHA/HFSA 2022 recommend initiating this therapy simultaneously from the time of diagnosis. However, implementation in practice, including in Indonesia, remains inconsistent. Lack of clinician understanding and the absence of these therapies in the JKN scheme pose additional barriers. Patient compliance issues, drug interactions, and monitoring of side effects also present challenges. Therefore, systematic strategies, education, and evidence-based policies are needed to ensure effective implementation of these therapies. These findings support the need for adaptation of global guidelines and the development of evidence-based policies to support the implementation of modern combination therapy for heart failure patients.